(untitled) (Studia Prawnicze / The Legal Studies, 2009)
Przedmiotem niniejszego opracowania jest problematyka stosowania w praktyce orzeczniczej Trybunału Konstytucyjnego (dalej też: Trybunał, TK) wyroków zawierających formułę „nie jest niezgodny”. Ewolucja orzecznictwa wykształciła ten specyficzny mechanizm procesowy dla oznaczenia relacji zachodzącej pomiędzy kwestionowaną regulacją a aktem normatywnym stanowiącym wzorzec kontroli. Celem artykułu jest omówienie tych sytuacji, w których Trybunał Konstytucyjny stosuje tę formułę, określenie jej znaczenia, a także wskazanie skutków wyroków o braku niezgodności. It is not specified in the Constitution nor in the Constitutional Tribunal Act what should be the exact formula of a ruling concerning constitutionality of the challenged normative acts. There are two main types of relationship between the normative acts which are indicated in the course of review of the norms, namely conformity and non-conformity. However, a ruling that the subject of the challenge conform or does not conform to the basis of review may not always precisely describe the relationship between the two norms. In some circumstances it is recommended to deploy other formula which will describe such relationship in a more adequate manner. In practice, a third formula of rulings has been developed in the jurisprudence of the Constitutional Tribunal, i.e. a ruling that a certain legal provision is not inconsistent with a specified constitutional provision. It differs in its meaning from the rulings on conformity and non-conformity. On the basis of the hitherto jurisprudence of the Constitutional Tribunal two sets of circumstances which lead the Tribunal to rule on the challenged provision’s lack of inconsistency with the normative act of higher rank may be distinguished. The formula is not inconsistent with has been applied both in order to confirm constitutionality of the challenged regulation and where the basis of review has been found inadequate with the challenged norm. At present the formula is not inconsistent with is extremely rarely used to indicate simple conformity. In the majority of cases it is applied in order to emphasise the lack of adequacy between the questioned regulation (the subject of a challenge) and the indicated normative act of higher rank (basis of review). If the basis of review is adequate with the subject of a challenge it means that there is a common ground of reference and the necessary connection between the two provisions that will enable an assessment of their interrelation. In the most recent Tribunal’s case law it is expressly underlined that it is the initiator of the proceeding that is under the duty to prove the adequacy between the norms. In the reasoning for his application he should bring forward arguments which will demonstrate, at least implicite, that the chosen basis of review is relevant and appropriate. Such a demonstration of the adequacy supplements the course of determining the scope of the constitutional review by defining the content of the provisions indicated as the basis of review and the subject of a challenge which are to be confronted against each other. In practice, the adequacy of the basis of review is often so obvious that there is no need for the Tribunal to put forward in the reasons for a ruling any arguments which will support it. The question of the kind of relationship existing between the subject of a challenge and the basis of review constitutes a first stage of the adjudication to the merits of the case in the proceedings before the Constitutional Tribunal. Where there is a lack of an adequate relation between those regulations, adjudication upon the constitutionality is objectively impossible since there is no appropriate ground for assessment of the challenged regulation. Failure to prove adequacy between the subject of a challenge and the basis of review results in an issuance of a judgment that the norms are not inconsistent. It should be qualified as an incomplete ruling as to the merits of the case. A judgment which includes a formula is not inconsistent with does not interfere in the actual legal system, nor does it directly affect the application of the challenged regulation in practice. However, it may indirectly affect courts’ rulings in particular cases. Being under the influence of the Tribunal’s judgment on the lack of inconsistency courts might refrain from applying particular regulations in some cases. Adjudication on the lack of inconsistency falls within the scope of the Tribunal’s competence to review hierarchical conformity of normative acts. It does not rebut the presumption of constitutionality of the challenged regulation. However, it also does not totally prevent subsequent review of the challenged regulation with the same basis of review. Such review wall be admissible providing that the adequacy between the challenged regulation and the basis of review will be pointed out and proven.